2008
DOI: 10.1007/s10308-008-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Migration decision from Bangladesh: permanent versus temporary

Abstract: More than 50% of the total migration from Bangladesh occurred from Sylhet, located to northern part of the country since the middle of the last century. This paper provides an empirical distinction between the temporary migrants (Bangladeshi citizens engaged in earning aboard) and the permanent migrants (those who have the dual citizenship) based on their cost conditions, earnings, and utilization of remittances in their country of origin. Temporary migrants' educational status, per capita income allocation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Gender issue, job opportunities, income differences, family welfare, remittances, temporary versus permanent migration, destination, networks etc. are some of the considerations at the family level which get pivotal importance while taking migration decision (Chattopadhyay, 2000;Joarder & Hasanuzzaman, 2008;Winters, Janvry, & Sadoulet, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Gender issue, job opportunities, income differences, family welfare, remittances, temporary versus permanent migration, destination, networks etc. are some of the considerations at the family level which get pivotal importance while taking migration decision (Chattopadhyay, 2000;Joarder & Hasanuzzaman, 2008;Winters, Janvry, & Sadoulet, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the environmental and socioeconomic challenges that Bangladesh faces, numerous studies have shown that migration, whether voluntary or forced, temporary or permanent and internal or external, has been one of the main features of life in the region since the 18th century (Siddiqui, 2003; Joarder and Hasanuzzaman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Using stratified sampling technique, we have interviewed 186 returned migrants to collect data from different areas of greater Sylhet region of Bangladesh as more than 50% of total migration from Bangladesh occurred from this region since the middle of the last century (Joarder and Hasanuzzaman 2008;Ahmad and Zohora 1997). The study areas were mainly Sylhet Sadar, Golapganj, Kulaura, Moulvibazar, Habiganj, Sunamgonj, Jagannathpur, Bishwanth, Fenchuganj, Bianibazar, Balaganj, Nabiganj, Chunarughat, Zuri, Rajnagar.…”
Section: Data Descriptionmentioning
confidence: 99%